2021
DOI: 10.3390/molecules26030582
|View full text |Cite
|
Sign up to set email alerts
|

Biocomputational Prediction Approach Targeting FimH by Natural SGLT2 Inhibitors: A Possible Way to Overcome the Uropathogenic Effect of SGLT2 Inhibitor Drugs

Abstract: The Food and Drug Administration (FDA) approved a new class of anti-diabetic medication (a sodium–glucose co-transporter 2 (SGLT2) inhibitor) in 2013. However, SGLT2 inhibitor drugs are under evaluation due to their associative side effects, such as urinary tract and genital infection, urinary discomfort, diabetic ketosis, and kidney problems. Even clinicians have difficulty in recommending it to diabetic patients due to the increased probability of urinary tract infection. In our study, we selected natural SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…These interactions remained in relative equilibrium during the dynamics and as a consequence are more likely to also interact when tested in vivo. The stability of the receptor–ligand complex is measured by conformational changes in the dynamic behavior of the complex [ 41 , 42 , 43 ]. RMSD values can vary throughout the stabilization process of the complex, which contributes to identifying the interaction or binding coupling between FimH proteins and binders [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…These interactions remained in relative equilibrium during the dynamics and as a consequence are more likely to also interact when tested in vivo. The stability of the receptor–ligand complex is measured by conformational changes in the dynamic behavior of the complex [ 41 , 42 , 43 ]. RMSD values can vary throughout the stabilization process of the complex, which contributes to identifying the interaction or binding coupling between FimH proteins and binders [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that the natural compound possessing the inhibitory action against both targets may be used as potential anti-diabetic agents having kisser side effects. In the study kurarinone showed potential binding (−7 kcal/mole) against an SGLT transporter but moderate binding (about −4 kcal/mole) with the FimH protein ( Mashraqi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 89%
“…The bacteria used to attach with the host cells by Type 1 pili (which possess FimH protein). Mashraqi et al (2021) studied the human SGLT transporter and bacterial FimH protein inhibition potential of natural flavonoids using computer aided drug discovery approach. It has been postulated that the natural compound possessing the inhibitory action against both targets may be used as potential anti-diabetic agents having kisser side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, phloretin, the hydrolysis product of phlorizin, demonstrated GLUT-inhibitory properties [ 64 ]. So far, several natural compounds have been identified as potential SLGT1 or SLGT2 inhibitors in various structure-based simulated scanning studies: (−)-kurarinone and sophoraflavanone G isolated from Sophora flavescens roots [ 65 ], gneyulins A and B isolated from the bark of Gnetum gnemonoides [ 66 ], farnesal and farnesol acyclic terpenoids extracted from Annona diversifolia Safford leaves [ 67 ], phlorizin, (+)-pteryxin, (+)-ε-viniferin [ 68 ], formononetin, and (+)-pteryxin [ 69 ]. However, these compounds have been evaluated only as potential antidiabetic agents, and, therefore, supplementary cytotoxicity studies are needed to assess their role in tumor glycolysis and their anticancer potential.…”
Section: Natural Regulators Of Aerobic Glycolysismentioning
confidence: 99%